A real options analysis of Australian wheat production under climate change1. (18th March 2015) - Sanderson, Todd; Hertzler, Greg; Capon, Tim; Hayman, Peter
Abstract : A significant portion of the world's agricultural systems currently operate at the extreme end of the climate conditions that are considered to be suitable for crop and livestock production. Under these conditions, even moderate climate changes are anticipated to drive substantial transformational changes to agricultural systems. Transformations require new investments and infrastructure and can leave some assets stranded. These transformations can be partially or wholly irreversible, and hysteresis effects can make switching difficult and mistakes costly to reverse. This study demonstrates how a real options decision framework, 'Real Options for Adaptive Decisions' (ROADs), can be used to investigate how uncertainties about the climate affect the adaptation and transformation of agricultural systems. By building upon recent developments in the mathematics of stochastic optimisation, we extend traditional economic analyses of agricultural investment decisions based on net present values to better represent incomplete knowledge and uncertainty. We report results from a case study in South Australia that describes the transition pathways farmers might follow as their industries are transformed in response to climate change.